Activity limitations of patients with stroke attending out-patient facilities in the Western Cape, South Africa - A. Rhoda; R. Mpofu; W. De Weerdt (AOSIS, 2011)
A stroke can affect individuals at the levels of impairment, activity and participation. The aim of this study is to determine the activity limitations  of stroke  patients  receiving  rehabilitation  at  out-patient  Community health Centres  (ChCs).  A  longitudinal  observational  study  was conducted.  Activity limitations  were  measured  using  the  Rivermead Motor  Assessment  Scale, the  Barthel  Index  and  the  nottingham extended  Activities  of  Daily  living scale  (neADl).  The  study  population consisted  of  100  patients  with  stroke consecutively admitted to the Community health Centres for therapy. The data was  analysed  using inferential  and  descriptive  statistics.  The  majority  of  the participants were not able to climb stairs, travel on public transport, wash dishes, do washing, do household chores and shopping, socialize and manage the garden at six months post stroke. A significant improvement was noted in the  ability  of  the  participants  to  perform  basic  activities  of  daily living  between  baseline  and  two  months,  but  not between two and six months. There was however a significant improvement in their ability to perform instrumental activities of daily living between two and six months. Although the participants were able to perform basic activities of  daily living enabling them to be independent in their homes, they were unable to perform instrumental activities of daily living which limited their functioning in the community. There is a need for therapists to include activities which could facilitate re-integration into the community in their rehabilitation of patients with stroke.